EFFECTIVENESS OF WEARABLE DEFIBRILLATORS: SYSTEMATIC REVIEW AND QUALITY OF EVIDENCE. (4th June 2014) - Uyei, Jennifer; Braithwaite, R. Scott
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The objectives of this systematic literature review were to identify all published literature on wearable defibrillators, assess the wearable defibrillator's efficacy and effectiveness in general and among specific patient groups, including post-myocardial infarction, post coronary artery bypass grafting or percutaneous coronary intervention, non-ischemic cardiomyopathy, and ischemic cardiomyopathy, and to evaluate the quality of evidence. Methods: The search and synthesis was informed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, and the quality of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation and the Newcastle Ottawa Scale. Results: A total of thirty-six articles and conference abstracts from thirty-three studies were included in the review. It appears that wearable defibrillator use compared with no defibrillator use reduces the chance of ventricular tachycardia and ventricular fibrillation (VT/VF) associated deaths by an absolute risk reduction of approximately 1 percent, achieved by averting approximately 4/5th of all VT/VF associated deaths. The quality of evidence was low to very low quality, such that our confidence in the reported estimates is weak. Conclusions: To validate beneficial results, further investigation using robust study designs conducted by independent researchers is warranted.